2001
DOI: 10.1248/cpb.49.622
|View full text |Cite
|
Sign up to set email alerts
|

Resazurin as an Electron Acceptor in Glucose Oxidase-Catalyzed Oxidation of Glucose.

Abstract: Resazurin (1) (cf. Chart 1) is known to act as an electron acceptor in diaphorase-or N-methylphenazinium methosulfate (PMS ϩ )-catalyzed oxidation of NAD(P)H and to be reduced to resorufin (2). [1][2][3][4][5][6][7][8][9] The reductively deoxygenated product 2 exhibits strong emission (excitation maximum at 563 nm and emission maximum at 587 nm in pH 7.4 buffer) 10,11) at wavelengthsϾ550 nm, where potential interference in analysis of colored or turbid serum components can be avoided. Thus, the transformation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 15 publications
1
11
0
1
Order By: Relevance
“…The fluorescence spectra of both forms of the probe show a maximum emission at 590 nm for resorufin and a negligible fluorescence for resazurin. In agreement with Maeda et al (27), we found that 570 nm is the optimal excitation wavelength of resorufin, although 530 nm is commonly used (5,15,28,29).…”
Section: Discussionsupporting
confidence: 92%
“…The fluorescence spectra of both forms of the probe show a maximum emission at 590 nm for resorufin and a negligible fluorescence for resazurin. In agreement with Maeda et al (27), we found that 570 nm is the optimal excitation wavelength of resorufin, although 530 nm is commonly used (5,15,28,29).…”
Section: Discussionsupporting
confidence: 92%
“…MTT (51), MTS (52) and Alamar Blue (53) are reduced by NAD(P)H-dependent oxidoreductase enzymes, while CTG (54) is reduced by cellular ATP. Several of these agents have previously proven unreliable in the presence of flavonoids.…”
Section: Discussionmentioning
confidence: 99%
“…Anaerobic conditions were verified by using 0.001% resazurin as a redox indicator (42,65). Microaerophilic and anaerobic conditions were observed at 8 and 23 min after the shift, respectively.…”
Section: Methodsmentioning
confidence: 99%